“Evangelizare pauperibus misit me”: ortodoxia e ortoprática dos padres lazaristas nas missões do Ceará (1870-1877) - SANTIROCCHI, Pryscylla Cordeiro Rodrigues (2019)
This work proposes an analysis of the actions of the French Lazarist priests belonging to the Congregation of the Mission in Ceará between the years of 1870 and 1877 in order to develop their congregational model during the religious missions in the interior of the province. At that time, the ultramontane reform, headed by the hierarchy of the Catholic Church, was at its peak and this congregation was one of the contributors to the process. However, this study intends to think of the Lazarists not only as reformist priests, but to reflect on the application of their model in Ceará. To do so, we will use institutional documents of the Congregation of the Mission, referring to France and Ceará, unpublished in researches in Brazil, crossing them with local documentation. Such a method will allow us to perceive the possible adaptations and conflicts, as well as the narratives constructed by them about an environment quite different from what they knew.